PENGARUH PENGETAHUAN, DUKUNGAN SUAMI, DAN TENAGA KESEHATAN TERHADAP PENGGUNAAN ALAT KONTRASEPSI PADA IBU MENIKAH DINI - Irma Mulyani; Alamsyah Aziz; Nunung Nurwanti (NHM PRESS, 2023)
The proportion of contraceptive use married women in early ages was 46%. The use of contraceptives in married women at early age is still low due to lack of knowledge, information and support. This study aims to analyze the influence of knowledge, support of husbands, and health workers on the use of contraceptives, and know the supporting and inhibiting factors in the use of contraceptives in mothers who married at an early age in West Bandung regency. The research method uses mixed methods with concurrent embedded design. A sample of 126 respondents using Multistage Random Sampling. Data collection was done by giving questionnaire and then selection of some informants to be interviewed. Data analysis used univariate, multivariate analysis (multiple logistic regression) and qualitative descriptive. The result showed 60,3% using contraception, 43,7% good knowledge about contraception, and 50,8% got support from husband and health worker in using contraception. Husband's support influences the use of contraceptives, while knowledge and support of health workers has no effect on the use of contraceptives. Husband support is the most influential factor on the use of contraceptives. Supporting factors in the use of contraceptives is the presence of information from health personnel. The inhibiting factor in the use of contraceptives is the absence of husband support. Suggested Local Government, health service and health worker to increase socialization through health promotion related to use of contraception by involving husband doing counseling.